A techno-economic and socio-environmental planning of wind farms for sustainable development and transition to a decarbonized scenario: Pakistan as a case study. (February 2023) - Shah, Mohammad Uzair; Khanum, Saeeda; Waqas, Adeel; Janjua, Abdul Kashif; Shakir, Sehar
Highlights: Identification of 3 to 5 sites in each province with highest wind potential. Utilization of GIS wind speed and SAM for feasibility analysis of 50 MW windfarm. RETScreen simulation to evaluate net equivalent carbon emission reduction. Conduction of online survey (n = 151) and site interviews at Jhimpir and Khuzdar. Policy recommendations from techno-economic and socio-environmental results. Abstract: Wind energy is a rapidly growing field of renewable energy in the world. The following study investigates potential locations throughout Pakistan with high suitability for wind farm deployment. Twenty locations throughout Pakistan, with 3 to 5 sites in each province, are selected. SAM and RETScreen are utilized for techno-economic and environmental feasibility analysis respectively. Social impact assessment is also an integral part of the study which is carried out by conducting online survey and site interviews. It is investigated that Sothgun demonstrated most suitable techno-economic feasibility while depicting largest capacity factor of 65.1 % with 287, 766 MWh annual electricity production. In contrast, Chakwal demonstrated the least capacity factor of 42.1 % with annual electricity production of 184, 398 MWh among the selected 20 locations. The LCOE ranged between 2.43 and 4.24 ¢/kWh with Manzoorabad showing the least and Chakwal showing the maximum. Similarly, payback period ranged between 4.2 (Sothgun) to 6.4 years (Chakwal). The net annual CO2e emissions reduction for Sothgun was evaluated to be 125, 466 tons with 54, 100, 008 L of unconsumed gasoline. The results of social assessment suggest that the government should include public awareness and participation schemes, financial incentives, efficient feed-in-tariffs and indigenization of wind technology into the next energy policy.